Workplace Based Assessments: The Innovation in Undergraduate and Postgraduate Medical Studies - Ikram Din Ujjan, M. Kashif Shaikh, Muhammad Khalid Sheikh, Syed Zulfiquar Ali Shah, Imran Karim, Samar Raza, Syed Jahanghir (Pakistan Journal of Medical & Health Sciences, 2023)
In traditional apprenticeship-training methods, students in health professions programs deal with real-world scenarios that test their knowledge and abilities like other physicians do.1 Assessment models must protect patients and give trainees contextual feedback2. Objective Structured Clinical Examinations (OSCEs), developed first by Ronald Harden while working at Dundee’s utilized in numerous teaching sectors for decades3. Assessments have limitations. Because of the nature of the stations, the doctor-patient encounter is generally broken down into its component parts, and the types of instances that can be repeated restrict patient concerns.4Many clinical lengthy case examination adjustments have been presented for viable answers. WPBA evaluates workplace clinical practices. It evaluates doctors’ practices. WPBA evaluates clinical trainees and provides comments. WBA has made the switch from numbers-based experience to organized assessment possible5. The General Medical Council; UK & Royal Colleges use WPBA to evaluate postgraduate medical students. In undergraduate medical education, WPBA is becoming popular.